Computational insights of hydrogen vacancies mediating interaction of lithium and sodium adatoms with an electrode graphane monolayer - Mapasha, Refilwe Edwin (University of Pretoria, 2023)
Dissertation (MSc (Physics))--University of Pretoria, 2023.